Utility of the visual system to monitor neurodegeneration in multiple sclerosis - Mey, Gabrielle M.; DeSilva, Tara M. (Frontiers in Molecular Neuroscience, 2023)
Neurodegeneration occurs early in the multiple sclerosis (MS) disease course and is an important driver of permanent disability. Current immunomodulatory therapies do not directly target neuronal health; thus, there is a critical need to develop neuroprotective strategies in MS. Outcome measures in clinical trials primarily evaluate disease activity and clinical disability scores rather than measures of neurodegeneration. The visual system provides a noninvasive correlate of brain atrophy and neuronal function through structural and functional exams. Furthermore, optic nerve axons and their respective neuronal cell bodies in the retina, in addition to their synaptic input to the thalamus, provide a distinct anatomy to investigate neurodegenerative processes. This review discusses the utility of the visual system as an early output measure of neurodegeneration in MS as well as an important platform to evaluate neuroprotective strategies in preclinical models.